Progress of antibiotic-loaded bone cement in joint arthroplasty - Xu, Yi-Ming (Chin Med J (Engl), 2020)
Bone cement, consisting of polymethyl methacrylate, is a bioinert material used for prothesis fixation in joint arthroplasty. To treat orthopedic infections, such as periprosthetic joint infection, antibiotic-loaded bone cement (ALBC) was introduced into clinical practice. Recent studies have revealed the limitations of the antibacterial effect of ALBC. Moreover, with the increase in high infection risk patients and highly resistant microbes, more researches and modification of ALBC are required. This paper reviewed latest findings about ALBC for most popular and destructive pathogens, summarized the influence of antibiotic kind, drug dosage, application method, and environment towards characteristic of ALBC. Subsequently, new cement additives and clinical applications of ALBC in joint arthroplasty were also discussed.